KAJIAN PENGAWASAN KONSTRUKSI PADA KEGAGALAN BANGUNAN DALAM PEMBANGUNAN GEDUNG BERTINGKAT TINGGI - Maiko Lesmana Dewa; Kiki Maria; Syamsu Marlin; Keti Andayani (LPPM Institut Pendidikan Nusantara Global, 2022)
ABSTRACT The essence of the research problem is how to obtain answers to research results related to construction supervision studies on building failures in construction work by obtaining answers to the following questions: development in general? Second, how is the legal protection for the community for building failure in construction work which causes harm to the community in connection with construction supervision responsibilities? Third, how is the settlement of legal disputes over building failures in construction work in Indonesia when linked to construction supervision rights? The research approach used and the development of the framework of thought in this study are based on a normative juridical approach by conducting an assessment of laws and regulations on building construction and construction, while the research method is a comparative method of various legal policies in several countries that regulate the pattern of interaction of development activities starting from the development stage. Preparation /planning to the stage of use. The findings in this study found that there is a role for legislation relating to construction supervision services in preventing building failures in building work.